A simple, reliable and robust reinforcement method for the fabrication of (RE)–Ba–Cu–O bulk superconductors. (30th March 2020) - Namburi, Devendra K; Huang, Kaiyuan; Lau, Wayne; Shi, Yunhua; Palmer, Kysen G; Dennis, Anthony R; Cardwell, David A; Durrell, John H
Abstract: Bulk high temperature superconductors (HTS) based on the rare-earth barium cuprates [(RE)BCO] have the potential to be applied in a variety of engineering and technological applications such as trapped field magnets, rotating electrical machines, magnetic bearings and flywheel energy storage systems. The key materials figure of merit for most practical applications of bulk superconductors is simply the product of the maximum current density that can be supported, which correlates directly with the maximum achievable trapped magnetic field, and the physical length scale over which the current flows. Unfortunately, however, bulk (RE)BCO superconductors exhibit relatively poor mechanical properties due to their inherent ceramic nature. Consequently, the performance of these materials as trapped field magnets is limited significantly by their tensile strength, rather than critical current and size, given that the relatively large Lorentz forces produced in the generation of large magnetic fields can lead to catastrophic mechanical failure. In the present work, we describe a simple, but effective and reliable reinforcement methodology to enhance the mechanical properties of (RE)BCO bulk superconductors by incorporating hybrid SiC fibres consisting of a tungsten core with SiC cladding within the bulk microstructure. An improvement in tensile strength by up to 40% has been achieved via this process and, significantly, without compromising the superconducting performance of the bulk material.